2022
DOI: 10.3390/cells11223616
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Dys-Homeostasis Contributes to APOE4-Associated AD Pathology

Abstract: The association of the APOE4 (vs. APOE3) isoform with an increased risk of Alzheimer’s disease (AD) is unequivocal, but the underlying mechanisms remain incompletely elucidated. A prevailing hypothesis incriminates the impaired ability of APOE4 to clear neurotoxic amyloid-β peptides (Aβ) from the brain as the main mechanism linking the apolipoprotein isoform to disease etiology. The APOE protein mediates lipid transport both within the brain and from the brain to the periphery, suggesting that lipids may be po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…APOE4 is a complex risk factor for AD and other neurodegenerative diseases, with multiple, heterogenous, and overlapping action mechanisms and molecular interactions [ 3 , 5 , 6 , 10 , 14 , 30 , 35 , 46 , 75 , 76 , 77 , 78 , 79 , 80 ]. Stuchell-Brereton et al [ 75 ] have shown that APOE4 is far more disordered and extended than previously described and retains conformational heterogeneity after binding lipids, which helps to understand the differences between the ε4 allele and protective variants of the protein.…”
Section: Apoe4 Brain Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…APOE4 is a complex risk factor for AD and other neurodegenerative diseases, with multiple, heterogenous, and overlapping action mechanisms and molecular interactions [ 3 , 5 , 6 , 10 , 14 , 30 , 35 , 46 , 75 , 76 , 77 , 78 , 79 , 80 ]. Stuchell-Brereton et al [ 75 ] have shown that APOE4 is far more disordered and extended than previously described and retains conformational heterogeneity after binding lipids, which helps to understand the differences between the ε4 allele and protective variants of the protein.…”
Section: Apoe4 Brain Effectsmentioning
confidence: 99%
“…Stuchell-Brereton et al [ 75 ] have shown that APOE4 is far more disordered and extended than previously described and retains conformational heterogeneity after binding lipids, which helps to understand the differences between the ε4 allele and protective variants of the protein. While there is not much controversy in stating APOE4 increases the risk of AD by driving earlier and more abundant amyloid pathology in the brains of APOE4 carriers [ 30 ], the work of Lazar et al [ 76 ] in mice expressing the human APOE4 vs. APOE3 isoform shows APOE4 carriers had altered cholesterol turnover, ratio imbalances of specific classes of phospholipids, low phosphatidylethanolamines bearing polyunsaturated fatty acids, and an elevation in monounsaturated fatty acids. More importantly, these changes in lipid homeostasis were related to increased production of Aβ peptides and higher levels of tau and phosphorylated tau in primary neuronal cultures [ 76 ].…”
Section: Apoe4 Brain Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ApoE cascade hypothesis does not include Aβ as a contributing factor in disease pathogenesis, stating that the biophysical and structural properties dependent of the ApoE isoform initiate a cascade of events driving AD and aging-related pathogenic condition (Martens et al, 2022). ApoE4 has been shown to alter lipid homeostasis and metabolism, leading to changes in lipid droplet formation, cholesterol turnover, and the PC/PE ratio (Farmer et al, 2019;Lazar et al, 2022;Yang et al, 2023). Consistent with MAM alterations, several lines of work support the involvement of ApoE in mitochondrial dysfunction as a contributing component to disease pathogenesis, including recent findings suggesting mitochondrial dysfunction influences ApoE expression and secretion (Dose et al, 2016;Martens et al, 2022;Wynne et al, 2023).…”
Section: Alzheimer's Disease and The Roles Of App And Aβmentioning
confidence: 99%